High-performance PEDOT:PSS-based thermoelectric composites. (October 2021) - Zhou, Hui; Chua, Ming Hui; Zhu, Qiang; Xu, Jianwei
Abstract : Over the past decades, poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) has emerged as one of the most attractive conducting polymers for organic electronics. In particular, PEDOT:PSS based composites have demonstrated its high potential as thermoelectrics. In this review, we aim to summarize the latest developments of PEDOT:PSS-based composite materials focusing on PEDOT:PSS/carbon nanostructures composites, PEDOT:PSS/tellurium composites, PEDOT:PSS/alloy composites, PEDOT:PSS/two-dimensional additives composites. The effects of various nanostructures such as nanoparticles, nanotube, nanowires and nanosheets on the thermoelectric properties of PEDOT:PSS was compared and discussed. The role of inorganic materials such as high-performance thermoelectric telluride-based alloys and certain two-dimensional materials e. g. SnSe, MoS2, as dopants in enhancing the thermoelectric properties of PEDOT:PSS composites was reviewed. The recent advances of post-treatment using some new chemical reagents such as dimethyl sulfone and sodium formaldehyde sulfoxylate to improve thermoelectric properties of PEDOT:PSS composites are also outlined. At the end, challenges and opportunities of PEDOT:PSS composites in enhancing the thermoelectric performance are commented. Highlights: This review summarizes the latest progress of thermoelectric PEDOT:PSS composites. A variety of PEDOT:PSS additives including carbon nanostructures, Te, Te-based alloys and 2D materials are reviewed. Thermoelectric devices made from PEDOT:PSS composite films are described.